Guidelines for Developing the Quality of Drinking Water Business Standards of Local Administrative Organizations: Guidelines for Developing the Quality of Drinking Water Business Standards of Local Administrative Organizations - Phaksupho, KonKhum (RATANABUTH JOURNAL, 2025)
Guidelines for developing the quality of tap water to meet the standards of drinkable water of local administrative organizations (LAOs) aim to raise the quality of tap water to be safe and suitable for consumption in accordance with the criteria of the Ministry of Public Health. It is an important mechanism for promoting public health at the community level. The development guidelines consist of 6 important aspects: 1) Upgrading the water production system to meet the standards by controlling the quality of raw water and using safe materials. 2) Regular water quality inspection and installation of water quality analysis systems. 3) Developing infrastructure such as pipe systems, water tanks, and reserve water sources. 4) Building the potential of personnel by training and arranging for water quality inspectors. 5) Public relations and creating community participation in water quality care. And 6) Applying various standards, such as those of the Ministry of Public Health and the Department of Groundwater Resources, as a framework for operations, along with using indicators according to the criteria of the Department of Local Administration to systematically certify the quality of drinkable tap water of local administrative organizations to deliver water supply services to local communities to enhance their quality of life.